Pemahaman Pajak E-Commerce, Sanksi Pajak, dan Kemudahan Akses terhadap Tingkat Kepatuhan Wajib Pajak dengan Kemauan Membayar Pajak sebagai Variabel Intervening - Wahyu Lesiana; Saiful Anwar (IPM2KPE, 2022)
This study aims to determine the effect of understanding e-commerce taxes, tax sanctions, and ease of access to taxes on the level of compliance of individual e-commerce taxpayers in the city of Surabaya on the online marketplace platform Shopee by using the willingness to pay taxes as the intervention variable. The research method used is quantitative method by collecting data using a questionnaire. The results showed that the coefficient value of the parameter on the tax understanding variable on the level of taxpayer compliance was 0.440 with a t-statistic of 3.168. The tax sanction variable shows a coefficient parameter value of -0.026 with a t-statistic of 0.249. The variable ease of access to taxes shows a coefficient parameter of 0.462 with a t-statistic of 2.933. Then, for the parameter value of the tax understanding coefficient on the willingness to pay taxes, it is known that it is 0.718 with a t-statistic of 13.278. The parameter value of the coefficient of tax sanctions on the willingness to pay taxes is -0.160 with a t-statistic of 1.564. The parameter value of the coefficient of ease of access to taxes on the willingness to pay taxes is known to be 0.428 with a t-statistic of 3.278. The parameter value of the coefficient of the level of taxpayer compliance on the willingness to pay taxes is known to be 0.124 with a t-statistic of 0.631. And testing on the intervention variables each has a parameter value of 0.089 with a t-statistic of 0.631 for the e-commerce tax understanding variable, a parameter value of -0.020 with a t-statistic of 0.548 for the variable tax sanctions, and a parameter value of 0.053 with a t-statistic of 0.616 for the variable ease of access to taxes. In conclusion, e-commerce tax understanding and ease of access to taxes have a positive and significant effect on the level of taxpayer compliance and willingness to pay taxes on Shopee e-commerce players in Surabaya City, while tax sanctions have a negative and insignificant effect on the level of taxpayer compliance and willingness pay taxes to Shopee e-commerce players in the city of Surabaya. In addition, understanding of e-commerce taxes and ease of access to taxes have a positive and significant effect on the level of taxpayer compliance through the willingness to pay taxes on taxpayers participating in e-commerce Shopee in Surabaya City, while tax sanctions have a negative and insignificant effect on the level of taxpayer compliance. through the willingness to pay taxes to the Shopee e-commerce taxpayer in the city of Surabaya. Keywords: Willingness to Pay Taxes, Ease of Access, Tax Understanding, Tax Sanctions